Serotoninergic and Circadian Systems: Driving Mammary Gland Development and Function - Suárez-Trujillo, Aridany; Casey, Theresa M. (Frontiers in Physiology, 2016)
Since lactation is one of the most metabolically demanding states in adult female mammals, beautifully complex regulatory mechanisms are in place to time lactation to begin after birth and cease when the neonate is weaned. Lactation is regulated by numerous different homeorhetic factors, all of them tightly coordinated with the demands of milk production. Emerging evidence support that among these factors are the serotonergic and circadian clock systems. Here we review the serotoninergic and circadian clock systems and their roles in the regulation of mammary gland development and lactation physiology. We conclude by presenting our hypothesis that these two systems interact to accommodate the metabolic demands of lactation and thus adaptive changes in these systems occur to maintain mammary and systemic homeostasis through the reproductive cycles of female mammals.